Pharmacokinetics and bioequivalence study of esomeprazole magnesium enteric-coated tablets 20 mg in healthy Chinese subjects under fasting and fed conditions - Ying Ding; Nannan Chu; Linling Que; Kai Huang; Yuanxing Chen; Wei Qin; Zhenzhong Qian; Yunfei Shi; Zhen Xu; Qing He (Frontiers Media S.A., 2023)
Objective: The main purpose of this study was to evaluate the pharmacokinetics, bioequivalence, and safety properties between a new generic and a brand reference formulation of esomeprazole enteric-coated tablets 20 mg in healthy Chinese subjects under fasting and fed conditions.Methods: The fasting study was an open-label, randomized, two-period crossover study conducted in 32 healthy Chinese volunteers, and the fed study was a four-period crossover study conducted in 40 healthy Chinese volunteers. Blood samples were collected at the specified time points and determined to obtain the plasma concentrations of esomeprazole. The primary pharmacokinetic parameters were calculated using the non-compartment method. Bioequivalence was analyzed by the geometric mean ratios (GMRs) of the two formulations and the corresponding 90% confidence intervals (CIs). The safety of the two formulations was assessed.Results: The fasting and fed study showed that the pharmacokinetics of the two formulations was similar. Under the fasting condition, the 90% CIs of GMRs of the test-to-reference formulation were 87.92%-104.36% for Cmax, 87.82%-101.45% for AUC0-t, and 87.99%-101.54% for AUC0-∞; under the fed condition, the 90% CIs of GMRs of the test-to-reference formulation were 80.53%-94.95% for Cmax, 87.46%-97.26% for AUC0-t, and 87.46%-97.16% for AUC0-∞. The 90% CIs of GMRs fall within the bioequivalence range of 80.00%-125.00%. The two formulations had good safety and were well-tolerated, and no serious adverse events occurred.Conclusion: According to relevant regulatory standards, esomeprazole enteric-coated generic and reference products exhibited bioequivalence and good safety in healthy Chinese subjects.Clinical Trials Registration:http://www.chinadrugtrials.org.cn/index.html, identifier CTR20171347 and CTR20171484